A Study on Evaluation of Apoptosis and Expression of Bcl-2-Related Marker in Wound Healing of Streptozotocin-Induced Diabetic Rats. (7th October 2013) - Bhan, Surya; Mitra, Rahul; Arya, A. K.; Pandey, H. P.; Tripathi, K.
Abstract : Uncontrolled blood sugar is a major cause of vascular complications and delayed wound healing in diabetes mellitus. During wound healing process, normally, apoptosis is responsible for events such as removal of inflammatory cells and evolution of granulation tissue into scar which occur during the late phase of wound healing. Early apoptosis can lead to abnormal wound healing by removing granulation tissue including fibroblast, endothelial cell, and small vessels. To determine the role of apoptosis in association with hyperglycemia in diabetic wound healing, apoptosis-related intracellular marker such as expression of Bcl-2 protein by immunohistochemistry and normal histology has been studied. Histological findings show higher level of apoptosis and diminished granulation tissue formation in diabetic rats wounds along with minimal expression of Bcl-2 in diabetic rats wounds when compared with nondiabetic rats wounds. It can be concluded from this study that elevated blood sugar level may be associated with increased apoptosis and the least expression of Bcl-2 protein which might cause deregulation of the wound healing processes in streptozotocin-induced diabetic rats.